Sobre as presenças e ênfases dadas ao tema da saúde na formação inicial em Educação Física no Centro de Educação Física e Desportos da Universidade Federal do Espírito Santo - Oliveira, Victor José Machado de (2018)
I investigated the presence and emphasis of health related themes in the educational curriculum for professionals pursuing a degree in Physical Education. I was inspired by cartography oriented research to follow frameworks and other procedures during the data collection process. I identified three main theoretical frameworks: 1) studies which investigated strategies of networking within the curriculum; 2) studies which expanded health related concepts and 3) studies focused around Giddens’ Structuration Theory. This field of research started to expand in 2017. I decided to focus on the routine within the training curricula for the Physical Education and Sports Center program of the Federal University of Espírito Santo. Initially, I gained access to Pedagogical Course Projects (PPC) for licenciate degree and bachelor’s degree Physical Education. After reading their documentation, I analyzed narratives and emerging topics related to health. I conducted semi-structured interviews with teachers who participated in the process of development of the documents. My first analysis focused on teachers as individuals. For such, I looked at curricula vitae and public health tenders oriented aspects of their education. I accessed their curricular experiences across four different disciplines. Two disciplines at bachelor’s degrees and two at licenciate degree. I documented field diaries for one semester. I have also conducted semistructured interviews with the teachers. The analysis of the data pointed to some hypotheses: 1) the political-epistemological orientations of teachers influences the conformation of the presences and emphases of the health theme in the training curricula; 2) however, these same orientations are not loose in the time-space being influenced (at the same time that they influence) the structure (duality of the structure); 3) the structure is composed of programs (REUNI, Pro-Health), policies and postgraduation that constrain the training curricula; these constraints create certain conditions of possibilities for the health theme. The analyzes of the data produced lead to the climax of the research when we observed five presences and two emphases of the health theme. We conceptualize presence as the objectification of empirical elements in which the health theme is assumed in the training curriculum. The presences are: disciplinary, of practice as the forming axis, minimum (or embryonic), curricular (or PPC narratives), and academic (or teacher training). Emphasis is understood as the effects generated by affections always linked to presences. The emphases are: technical-scientific, biophysiological and biomedical; and pedagogical, public and collective. The presences and emphases point to two paths that are produced for the formation of the area. The first corresponds to the hegemony based on the Natural and Biological Sciences that reduces the possibility of listing an expanded perspective of health. The second is linked to the emergence of other paths from the Social and Human Sciences and Collective Health. We observe potentialities to outline other directions and training policies in Physical Education for dealing with health in a variety of fields. The strengthening of emphases related to Social and Human Sciences and Collective Health in training curricula are important. These perspectives have allowed us to look in other ways at the complex phenomenon that Physical Education deals with, which is the human body movement in its interface with corporal practices. It is necessary to continue along this path, reaffirming training policies that enhance SUS, contexts, meetings, people; in short, life beyond a concept of health restricted to the subject of disease